Mengurangi Laju Kerusakan Jalan dengan Menggunakan Metode RCI (Road Condition Index) di Kabupaten Madiun - Bangun Prasetya; Yosef Cahyo Setianto Poernomo; Sigit Winarto; Rendy Kurnia Dewanta; Faiz Muhammad Azhari (Faculty of Engineering, Kadiri University, 2021)
Road construction is an important infrastructure in supporting smooth mobility. Proper maintenance of road conditions needs to be done to minimize the occurrence of traffic accidents. The purpose of this study is to determine the road conditions on roads in Madiun Regency. The research carried out includes observing the type of damage and the handling that must be carried out on these roads. Observations are made by dividing the observation points into 5 locations. The method used is by using the Road Condition Index (RCI), namely by visual means and referring to the Minister of Public Works Regulation No. 19 of 2011. The results showed that 5 roads in Madiun Regency are in good condition along 3,775 Km (15.8%), 11,357 Km in moderate condition. (47.6%), 7,272 Km (30.5%) lightly damaged and 1,436 Km (6.1%) heavily damaged. The need for handling the road conditions includes routine maintenance of 15.8%, periodic maintenance of minor damage by 47.6%, periodic maintenance of moderate damage by 30.5%, and an increase of 6.1%.